(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The effect of dimethyl- and diethylsulfones on the thermal denaturation of DNA was studied by UV/vis, fluorescence spectroscopy and densimetry. It is revealed, that sulfones show expressed denaturing ability. The denaturing ability of sulfones increases with the increasing of carbon chain length of sulfones, which indicates the contribution of hydrophobic interactions.